Linear Driving Force Model for Adsorption onto Activated Carbon Monolith - Darmadi, Darmadi; Choong, Thomas S.Y.; Chuah, T. G.; Yunus, Robiah; Yap, Taufiq Y.H. (Jurnal Rekayasa Kimia & Lingkungan, 2006)
A mathematical model on carbon coated monolith using the linear driving force model is develop. The computer program is writted in MATLAB and simulation using data from [4] for cell density 200 cpsi was used to studies the effect of different variables on breakthrough profiles. The result showed that the breakthrough curve of the monolith is very sharp. Because of its an open structure and lower pressure drop, monolith is an attractive alternative internals for separation.Keywords: Adsorption, modeling, simulation, carbon coated monolith, breakthrough